Biochemical studies of amylase, lipase and protease in Callosobruchus maculatus (Coleoptera: Chrysomelidae) populations fed with Vigna unguiculata grain cultivated with diazotrophic bacteria strains - Silva, L. B.; Torres, B.; Nóbrega, R. A.S.; Lopes, G. N.; Vogado, R. F.; Pavan, B. E.; Fernandes-Junior, P. I. (Cambridge University Press (CUP), 2017)
The objective of this study was to evaluate the enzymatic activity of homogenates of insects fed on grain of cowpea, Vigna unguiculata (L.), cultivars grown with different nitrogen sources. For the experiment we used aliquots of the homogenate of 100 unsexed adult insects, emerged from 10 g of grain obtained from four cowpea cultivars: ‘BRS Acauã’, ‘BRS Carijó’, ‘BRS Pujante’, and ‘BRS Tapaihum’ grown under different regimes of nitrogen sources: mineral fertilizer, inoculation with strains of diazotrophs (BR 3267, BR 3262, BR 3299; INPA 03–11B, 03–84 UFLA, as well as the control (with soil nitrogen). The parameters evaluated were enzymatic activities of insect protease, amylase and lipase and the starch content of the grains. There were differences in the enzymatic activity of amylase, lipase and protease of insect homogenate according to the food source. A lower activity of the enzyme amylase from C. maculatus homogenate was observed when insects were fed grain of the cultivar BRS Carijó. A lower activity of lipase enzyme from C. maculatus homogenate was observed when the insects fed on grain from the interaction of the cultivar Tapaihum inoculated with BR 3262 diazotrophs. The lowest proteolytic activity was observed in homogenate of insects fed on interaction of ‘BRS Carijó’ inoculated with BR 3262 diazotrophs. Starch content correlated positively with the amylase activity of C. maculatus homogenate. The cultivar BRS Carijó had a different behavior from the other cultivars, according to the cluster analysis.
Keywords: carbohydrate metabolism; cowpea weevil; digestive enzyme; nitrogen fertilization; nitrogen fixation